Dataset on the dissemination of genetically improved carp in Bangladesh - Benzie, John; Yeasin, Mohammed; Ali, Md. Rayhan; Fakhruddin, Md.; Dam Lam, Rodolfo; Hamilton, Matthew (2023)
It contains data on the dissemination of G3 rohu from hatcheries and nurseries to farmers in 2022 to assess the adoption of the improved fish strain in Bangladesh.